Analisis Kreativitas Anak Usia Dini Melalui Kegiatan Menggambar di RA Bina Wanita Bahagia - Rodiatul Janah; Ratu Yustika Rini; Novita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The research was carried out because of the lack of children's creativity in drawing activities, during drawing activities the children wanted to make drawings by the teacher because they were not able to make a picture according to their wishes so they asked for help from the teacher to draw according to the child's wishes, the children drew almost the same as their classmates. Research This aim is 1. to bring out the creativity of young children through drawing activities at Rauhdatul Atffal (RA) Bina Anita Bahagia planning the city of Serang 2. To find out the implementation of drawing activities for young children at Rauhatul Atffal (RA) Bina Wanita Bahagia. Drawing activities can bring out the creativity of young children in drawing and imagining what they see around them, such as from the school environment, home environment, their surroundings or others. Drawing activities using drawing media around the school in the form of posters, picture cards, pictures on the school walls and using drawing tools to draw. This research aims to describe the creativity that can emerge in young children through drawing activities using drawing media and drawing tools at Raudatul Atffal Bina Wanita Bahagia with subjects in group B1 as many as 12 children with 2 teachers as resource persons. This research uses a descriptive qualitative approach. Researchers use data collection techniques which include interviews, observation and documentation. The instruments used are instruments that comply with interview and observation guidelines. The research results show that the creativity of the RA Bina Wanita Happy Group B1 children in using drawing media located around the school and drawing tools shows good results. This is proven by the way all the B1 group children draw pictures with various patterns by mixing colors using colored pencils. or crayons according to the imagination of young children by implementing their ideas from what they see and putting it into their drawings, children dare to tell the results of their work in front of the class, and are able to express their opinions and great curiosity.